(untitled) (Herald of Journalism, 2016)
TIn this article are considered M.Zhumabayev’s poems « Aida atyndy , Sarsenbay», «Shoyyn Jol», «Zhazdy kүnі kalada» which was written on environmental issues. In this article is opened hidden subtext of these works. Revealed that the socio-political position of people more important than environmental issues. The main idea is comprehensively analyzed. The ideological content of the poems are analyzed with the help of taking historical information and opinions investigators of Magzhan Zhumabaev. Also considered the creation of people’s image, still reeling from hunger. Keywords: .